LEARNING MANAGEMENT BASED ON DAVIES’ CONCEPT TO PROMOTE PIN (FOLK INTRUMENT) PRACTICE SKILLS FOR GRADE 12th STUDENT - piapeng, Anocha; Pantasri, Pittayawat (Journal for Developing the Social and Community, 2023)
This research aims to Develop learning management according to Davies’ concept to promotes the practice of playing the Pin to be effective 70/70. Comparison of the practice skills of playing the Pin after the lesson against the 70 percent threshold. Compare student achievement. Against the 70 percent threshold and to study the student’s satisfaction towards the learning management according to Davies’ concept. The sample group used in this research were Mathayomsuksa 6/8 students at NongRuea Wittaya School. KhonKaen Educational Service Area Office, semester 2, academic year 2022, 32 people which was obtained by cluster random sampling, using the classroom as the random unit. The research tools consisted of 1) Learning management plan on Isan Pin folk instrument practice, amount 20 learning plans. 2) Learning achievement test on Isan Harp folk music theory 20 items. 3) Isan Pin folk music practice skills assessment form, 5 items. 4) Satisfaction questionnaire 15 items. the statistics used in the data analysis were percentage, standard deviation. and statistical T-test One-Group Posttest Design. The research findings were as follows : 1) Davies’ concept of learning management which promotes effective Pin playing skills for Mathayomsuksa 6 students E1/E2 equal to 78.56/86.48 which is higher than the specified criteria. 2) Mathayom 6 students had scores for playing the Pin that passed the criteria, 29 people, accounting for 96.66 percent, did not pass the criteria, 3 people, accounting for 3.34 percent, overall the score was 81.25 percent. ( = 16.25, S.D. = 1.81) 3) Mathayom 6 students had academic achievement scores of 32 students who passed the criteria, calculated as 100 percent, did not pass the criteria 0 people, calculated as 0 percent. Overall, the score was 90.62 percent. ( = 18.13, S.D. = 1.95) 4.) The satisfaction of the learners towards the learning management according to Davies’ concept. The overall mean was at the most satisfactory level( = 4.85, S.D. = 0.10)